2023
DOI: 10.3389/fmed.2023.1192070
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Regression of Glioblastoma after flavivirus infection

Abstract: Glioblastoma is the most frequent and aggressive primary brain cancer. In preclinical studies, Zika virus, a flavivirus that triggers the death of glioblastoma stem-like cells. However, the flavivirus oncolytic activity has not been demonstrated in human patients. Here we report a glioblastoma patient who received the standard of care therapy, including surgical resection, radiotherapy and temozolomide. However, shortly after the tumor mass resection, the patient was clinically diagnosed with a typical arbovir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Serum analysis found the presence of antibodies versus ZIKV. The patient experienced total remission, and the situation remained stable over the following six years [24]. In the present study, for the first time, we have demonstrated that the oncolytic effect of ZIKV could also target pancreatic NETs (Figure 11) due to their neural origin.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Serum analysis found the presence of antibodies versus ZIKV. The patient experienced total remission, and the situation remained stable over the following six years [24]. In the present study, for the first time, we have demonstrated that the oncolytic effect of ZIKV could also target pancreatic NETs (Figure 11) due to their neural origin.…”
Section: Discussionsupporting
confidence: 59%
“…Our strong interest in this virus is driven by its marked ability to specifically target glioblastoma cells, with no reported effect on other cell types, except on NSCs during the developmental stage [23]. In this regard, a case report described a possible fortuitous infection in a glioblastoma patient [24]. During a ZIKV outbreak in Brazil, the patient was subjected to neurosurgery after glioblastoma diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…After surgery, the patient had radiotherapy and chemotherapy with TMZ; however, a few weeks later she became infected with ZIKV. Six years after this, the patient remained in remission with no GBM recurrence despite carrying wild-type copies for the IDH1 and IDH2 genes together with mutations in oncogenes such as PIK3CA, clinically associated with patients who develop GBM at a young age and who had a poor survival prognosis [ 73 ]. The latter highlights the low toxicity that ZIKV seems to have in adults, which might support the clinical translation of WT ZIKV in controlled trials.…”
Section: Zikv Therapy In Gbmmentioning
confidence: 99%
“…In a recent study, investigators presented an interesting case involving a patient with glioblastoma who underwent the conventional standard-of-care therapy, including surgical resection, radiotherapy, and temozolomide administration [ 47 ]. Interestingly, at about the same time as the tumor-mass resection, the patient was simultaneously afflicted with a clinical diagnosis reminiscent of an arbovirus-like infection, which transpired during a Zika virus outbreak in Brazil.…”
Section: Oncolytic Virotherapymentioning
confidence: 99%
“…After the successful resolution of the infection, a profound regression of the glioblastoma occurred, accompanied by the absence of any recurrence. This remarkable clinical response was consistently sustained, enduring for a remarkable span of 6 years (7 years now) following the initial diagnosis of glioblastoma [ 47 ]. ZIKV has shown oncolytic capacity, able to infect and trigger cell death mainly in the glioblastoma stem-like cell populations (Sox2+Ki67+) in vitro and in vivo, in animal models [ 48 , 49 , 50 ].…”
Section: Oncolytic Virotherapymentioning
confidence: 99%